2021
DOI: 10.1111/nuf.12670
|View full text |Cite
|
Sign up to set email alerts
|

Household emergency preparedness: A multidisciplinary concept analysis

Abstract: Background: Household emergency preparedness, at the individual and family micro-level, is often identified as below national disaster preparedness standards.Aims: Conceptual clarity of household emergency preparedness is foundational for disaster preparedness research, theory construction, and instrument use.Materials & Methods: Adhering to Walker and Avant's (2019) concept analysis method, the purpose of this paper is to outline the concept of household emergency preparedness by identifying the uses of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…I have enough…I am in a position that this is an inconvenience, it’s not a disaster.” This conceptualization is consistent with widely accepted views of disasters as events where the required capacity or ability to cope exceeds available resources(53). Another respondent stated, “Everyone is vulnerable depending on where you are, what you’re doing and what the impact is but there are certain people who are much more vulnerable because they don’t have the resources or the ability to be resilient.” In a recent multidisciplinary review of literature and concept analysis of household emergency preparedness, authors examined antecedents, or things that must occur prior to the concept (disaster) occurrence(54). Personal resources/financial capital was not included as an antecedent to household emergency preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…I have enough…I am in a position that this is an inconvenience, it’s not a disaster.” This conceptualization is consistent with widely accepted views of disasters as events where the required capacity or ability to cope exceeds available resources(53). Another respondent stated, “Everyone is vulnerable depending on where you are, what you’re doing and what the impact is but there are certain people who are much more vulnerable because they don’t have the resources or the ability to be resilient.” In a recent multidisciplinary review of literature and concept analysis of household emergency preparedness, authors examined antecedents, or things that must occur prior to the concept (disaster) occurrence(54). Personal resources/financial capital was not included as an antecedent to household emergency preparedness.…”
Section: Discussionmentioning
confidence: 99%
“…This section includes two entries (one single-choice entry, and one multiple-choice entry). The entries in this part were designed based on market research on the current first-aid kit, a review of relevant literature, and expert consultation (18)(19)(20)(21)(22)(23)(24).…”
Section: Items For Residents' Home First-aid Kit Preparation Behaviormentioning
confidence: 99%
“…Wilcox et al [ 45 ] in their analysis of household emergency preparedness, highlight that nurses should prepare emergency overnight bags in case they are unable to leave the hospital due to severe weather or other emergencies. They should arrange, where necessary, backup carers for children or pets in the event of extended shifts or being unable to return home safely [ 45 ]. Balut et al [ 44 ] found that USA healthcare workers who felt they were not prepared at a household level for major emergencies were more open to receiving preparedness training.…”
Section: Introductionmentioning
confidence: 99%
“…While a number of studies have examined nurses' emergency household preparedness, none have compared how prepared nurses feel (perceived preparedness) and their actual preparedness (checklist preparedness) [28,30,[44][45][46][47]. Wilcox et al [45] in their analysis of household emergency preparedness, highlight that nurses should prepare emergency overnight bags in case they are unable to leave the hospital due to severe weather or other emergencies. They should arrange, where necessary, backup carers for children or pets in the event of extended shifts or being unable to return home safely [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation